Public Relations Strategy of Islamic Education Institutions - Ayulan , Marsha Latipus (MID Publisher International, 2024)
Homo Socius, it means that man as a social being. Man as a social being can not live without interaction with another individual or group. Not only individuals but also an institution has to interact with the public for its development. A school is an institution that provides education. So, a school has to establish and maintain internal & external relations to maintain education quality. However, there are still many internal and external conflicts in school. To maintain education quality and develop the school, a school has to implement a public relations strategy to get support from its internal and external public. The purpose of the research is to find out public relations strategy in internal and external schools, including the problem. And to increase awareness and understanding of the school’s public relations. The paradigm of the research is constructivism, the research approach is a case study, and the research method is qualitative. The result of the research. The public relations division school has not been officially formed yet, it is managed by non-experts, it has a position under the headmaster, and it is focused on the external public. First, internal relations. The headmaster is always telling about “how to communicate in good ways” to the internal public to preserve internal communication, and the headmaster is always reminds about the motto, working culture, policy, etc, to the internal public in good ways. Also, five effective internal media and four employee relations programs have been applied. Second, external relations. The school has established cooperation with local communities, and the school has preserved the relation with visiting local communities, making events with involve the communities, and helping the local economy. Also, the school has established cooperation with local education authorities, and the school does its tasks and follows the instructions to preserve the cooperation. The last one, the problems of implementation of public relations strategy are human resources, problems of internal communication, and budget.